Kristus algoritmik: Kecerdasan buatan, teologi digital, dan masa depan diskursus Kristologi - Daud Darmadi (KURIOS, 2025)
This study investigates the intersection of advances in artificial intelligence technology and contemporary Christology through the concept of the "Algorithmic Christ" as a theological framework. Using a constructive hermeneutic approach that integrates textual studies of classical Christology and contextual interpretations of digital reality, this study analyzes four key aspects: the manifestation of the incarnation in the virtual world; the algorithmic model of consciousness for understanding the duality of Christ's nature; the function of algorithms as a means of divine revelation; and the pastoral impact on the life of faith in the digital age. The results reveal that AI technology does not replace conventional Christology but rather opens a hermeneutical perspective that enriches the concept of the incarnation and the universal presence of Christ. Algorithms are considered a medium of revelation that reveals divine patterns in digital structures while still acknowledging the limitations in representing transcendent mystery. Pastoral implications include the urgency of algorithmic literacy, the rejection of algorithmic bias, and the development of a spirituality that can navigate the complexities of the digital world. The contribution is the development of a "digital theology" that is responsive to the challenges of contemporary technology while maintaining the integrity of the Christian message.   Abstrak Penelitian ini menginvestigasi pertemuan antara kemajuan teknologi kecerdasan buatan dan kristologi masa kini melalui konsep "Kristus Algoritmik" sebagai kerangka teologis. Dengan pendekatan hermeneutika konstruktif yang mengintegrasikan kajian tekstual kristologi klasik dan interpretasi kontekstual realitas digital, studi ini menganalisis empat aspek kunci: manifestasi inkarnasi dalam dunia virtual; model kesadaran algoritmik untuk memahami dualitas kodrat Kristus; fungsi algoritma sebagai sarana wahyu ilahi; serta dampak pastoral dalam kehidupan iman di zaman digital. Hasil penelitian mengungkap bahwa teknologi AI bukan pengganti kristologi konvensional, melainkan membuka perspektif hermeneutis yang memperkaya konsep inkarnasi dan kehadiran universal Kristus. Algoritma dipandang dapat menjadi medium revelasi yang mengungkap pola-pola divine dalam struktur digital, meski tetap mengakui limitasi dalam merepresentasikan misteri transenden. Implikasi pastoral meliputi urgensi literasi algoritmik, penolakan bias algoritma, dan pengembangan spiritualitas yang mampu bernavigasi kompleksitas digital. Kontribusinya adalah pengembangan "teologi digital" yang responsif terhadap tantangan teknologi kontemporer sambil memelihara integritas pesan Kristiani.